License to Critique: A Communication Perspective on Sustainability Standards. Issue 2 (13th February 2017) - Christensen, Lars Thøger; Morsing, Mette; Thyssen, Ole
ABSTRACT: Sustainability standards are important governance tools for addressing social and environmental challenges. Yet, such tools are often criticized for being either too open-ended or too restrictive, thereby failing to contribute significantly to the development of sustainable practices. Both dimensions of the critique, however, miss the point. While all standards in principle combine elements of openness and closure, both of which are necessary to keep the sustainability agenda relevant and adaptive, sustainability standards often operate in contexts that favor closure. In this article, we draw on a research tradition that views communication as constitutive of organization to emphasize the significance of communicative mechanisms that stimulate organizational openness in the application of standards. With the notion of "license to critique, " we present a managerial philosophy designed to involve managers and employees, mobilize and develop their knowledge about sustainability and bring it forward for the benefit of both the organization and the environment.